L2 writing self-efficacy, task-value, and strategies of Malaysian undergraduate students - Raoofi, Saeid (2014)
This study seeks to investigate the relationship between self-efficacy, task value, strategy use and performance in ESL writing. There were four overarching purposes of the present study: (a) to determine and describe Malaysian undergraduates’ ESL writing value, self-efficacy and strategies, (b) to determine how students ESL writing value (utility value, intrinsic value, attainment and cost) is related to their writing proficiency (c) to examine the types of writing strategies that enable ESL students to develop their writing ability, and (d) to investigate the interrelationships between ESL writing task value, self-efficacy, strategy use and performance. The sample of the study consisted of 304 Malaysian undergraduate students learning English as a second language at Unveristi Putra Malaysia. Participants were drawn from a writing course. A mixed method design was used in this study. In the first phase, data was collected through questionnaires and writing performance tests. In the second phase, qualitative data was collected through interviews and focus group discussions to get a better insight into learners’ strategies, values, beliefs and motivation about their ESL writing skill. With respect to data analysis, multiple regression, ANOVA and correlational analyses were used for the quantitative part. For the qualitative part, all the answers to the open-ended questions and interviews were carefully analyzed to detect codes and themes. The results showed detailed description of ESL writing task value, self-efficacy and strategies of Malaysian undergraduates. Overall, the students had a medium level of ESL writing self-efficacy. It was found that students with higher writing abilities as measured by writing proficiency tests, had higher level of writing self-efficacy compared with those with intermediate and lower writing proficiency. The students placed high utility value and attainment value on their writing, while they attributed medium intrinsic value to their writing. Students in high proficiency group attributed significantly higher intrinsic value and attainment value than those in low proficiency group. It was also found that Effort regulation writing strategy and metacognitive writing strategy were reported as the first and second most frequently used strategies respectively while social strategy was reported as the least frequently used category. The results also showed that students with higher writing ability reported using significantly more metacognitive, cognitive, affective and effort regulation strategies than those with lower writing proficiency. Regression analyses revealed that self-efficacy and utility value emerged as the best predictors of writing strategy use. Results of regression analyses also revealed that intrinsic value and self-efficacy contributed significantly to the prediction of writing performance. The qualitative findings supported quantitative results. The Qualitative findings also revealed that several factors such as mother tongue influence and grammatical knowledge of English language emerged as important determinants in writing self-efficacy. Implication of these results for future research and ESL teaching are discussed.